2023
DOI: 10.3390/ijms24108854
|View full text |Cite
|
Sign up to set email alerts
|

Blood T Helper Memory Cells: A Tool for Studying Skin Inflammation in HS?

Abstract: Hidradenitis suppurativa (HS) is an inflammatory skin disease characterized by painful lesions on intertriginous body areas such as the axillary, inguinal, and perianal sites. Given the limited treatment options for HS, expanding our knowledge of its pathogenetic mechanisms is a prerequisite for novel therapeutic developments. T cells are assumed to play a crucial role in HS pathogenesis. However, it is currently unknown whether blood T cells show specific molecular alterations in HS. To address this, we studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, the metabolism of blood CD4 + T cells appears to also be altered in HS patients. In fact, it was recently found that the expression of several genes involved in oxidative phosphorylation was downregulated in the blood CD4 + T cells of HS patients and a few transcripts for glycolysis-dependent energy production were increased [63].…”
Section: Proinflammatory Mechanisms Of Obesitymentioning
confidence: 99%
“…Interestingly, the metabolism of blood CD4 + T cells appears to also be altered in HS patients. In fact, it was recently found that the expression of several genes involved in oxidative phosphorylation was downregulated in the blood CD4 + T cells of HS patients and a few transcripts for glycolysis-dependent energy production were increased [63].…”
Section: Proinflammatory Mechanisms Of Obesitymentioning
confidence: 99%